Anthropometry, physical performance, and ultrasound patellar tendon abnormality in elite junior basketball players: a cross-sectional study. Issue 2 (23rd March 2004) - Cook, J L; Kiss, Z S; Khan, K M; Purdam, C R; Webster, K E
Abstract : Objective: Patellar tendinopathy has been reported to be associated with many intrinsic risk factors. Few have been fully investigated. This cross-sectional study examined the anthropometric and physical performance results of elite junior basketball players with normal or abnormal patellar tendons to see if any measures were associated with changes in tendon morphology. Methods: Agility, leg strength, endurance, and flexibility were measured in 71 male and 64 female players. A blinded radiologist ultrasonographically examined their patellar tendons and athletes were grouped as having normal or abnormal tendons. One-way ANOVA was used to test for differences in anthropometric and physical performance data for athletes whose tendons were normal or abnormal (unilateral or bilateral tendinopathy) on ultrasound. Results: Results show that females with abnormalities in their tendons had a significantly better vertical jump (50.9±6.8 cm) than those with normal tendons (46.1±5.4 cm) (p = 0.02). This was not found in males. In males, the mean sit and reach in those with normal tendons (13.2±6.7 cm) was greater (p<0.03) than in unilateral tendinopathy (10.3±6.2 cm) or in bilateral tendinopathy (7.8±8.3 cm). In females, those with normal tendons (13.3±4.8 cm) and bilateral tendinopathy (15.8±6.2 cm) were distinctly different from those with unilateral tendinopathy (7.9±6.6 cm). Conclusion: Flexibility and vertical jump ability are associated with patellar tendinopathy and the findings warrant consideration when managing young, jumping athletes.